Association of aortic valve disease with intestinal angioectasia: data from the Nationwide Inpatient Sample. Issue 4 (April 2018) - Jehangir, Asad; Pathak, Ranjan; Ukaigwe, Anene; Donato, Anthony A.
Abstract : Objective: Since the description of a correlation between aortic stenosis and angioectasia, controversy has persisted about whether these diseases are truly associated or coincidental findings of older age. Our objective was to determine the association of aortic valve disease and bleeding intestinal angioectasia from a large database. Patients and methods: We used the 2011 Nationwide Inpatient Sample database to identify hospitalizations in the USA in patients with bleeding intestinal angioectasia. International Classification of Diseases, 9th revision, Clinical Modification codes were used to identify patients with aortic valve disease, mitral valve disease, and known risk factors for angioectasia (including diagnosed von Willebrand disease, left ventricular assist device, and chronic kidney disease). Univariate and multivariate logistic regression were used to determine the odds of association between the valvular diseases and angioectasia. Results: A total of 32 079 intestinal angioectasia-related hospitalizations were identified of which 7.02% ( n =2253) cases had coexistent aortic valve disease. The unadjusted odds of aortic valve disease in association with bleeding intestinal angioectasia versus those without bleeding angioectasia was 4.95 [95% confidence interval: (CI): 4.43–5.54, P <0.001]. The association of intestinal angioectasia with mitral valve disease was not significant (odds ratio=1.56, 95% CI: 0.59–4.14, P =0.38). When adjusted for age and known risk factors, the odds of aortic valve disease in bleeding intestinal angioectasia was still significant (odds ratio=2.37, 95% CI: 2.10–2.66, P <0.001). Conclusion: Our findings support an important association between aortic valve disease and bleeding intestinal angioectasia, not identified in valvular heart valvular diseases with lower shear stress (mitral valve disease).